An Application of Learning Organization Theory to Increase Organizational Efficiency of Business Companies in Bangkok - Pon Putthanukorn, Wijit Thongnun, Ali Khan, Weechapiphat Phasuk, Nuntaporn Rattananda; Anusorn Sathaporn,Atanop Dejnarong, Prapatson Samapat, Sinlapachai Watcharachawakul,Wanwisa Rodpai (South Eastern European Journal of Public Health, 2025)
The purposes of this research were: 1) to study an application of learning organization theory of modern business companies; 2) to study organizational efficiency of modern business companies; and 3) to study an application of learning organization theory influencing organizational efficiency of modern business companies. The samples used in this study were 375 employees working in business companies in Bangkok, Thailand. The research results showed that the overall learning organization of business companies in Thailand was at a high level. In particular, organizational transformation had the highest mean value, followed by learning technology, learning dynamic, knowledge management and personnel empowerment. Organizational efficiency of business companies, in total, was perceived at high level. In particular, personnel management had the highest mean value, followed by task management, and material resource management respectively. The results of the analysis on the influence of learning organization theory on organizational efficiency of business companies, using multiple regression analysis with the Enter method, revealed that an application of learning organization theory significantly influences organizational organizational efficiency at the .01 and .05 levels (F = 60.325, p = .000). The components of learning organization theory that has the most significant impact on organizational efficiency was learning dynamics, followed by organizational transformation, learning technology, personnel empowerment, and knowledge management respectively.